Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/adsc.200700114
|View full text |Cite
|
Sign up to set email alerts
|

A New Solid‐Phase Reaction System Utilizing a Temperature‐ Responsive Catalyst: Oxidative Cyclization with Hydrogen Peroxide

Abstract: A switchable catalyst based on temperature change provides a novel solid-phase reaction system in water. An increase in catalyst affinity for organic substrates at higher temperature led to efficient activity driving the solid inner-phase reaction, and loss of affinity at lower temperature allowed easy separation of organic products upon completion of the reaction. Application of this catalyst intelligence to design a novel catalytic system brought about an efficient oxidative cyclization with hydrogen peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Synthetic methodology for the synthesis of 5 has been reported; examples are the oxidative cyclization reaction of 5-hexen-1-ol [55][56][57] using TS-1 (60°C, 6 h) [55,56] or a PNIPAAm-PW 12 O 40 3-complex (60°C, 6 h) [57] to give 90 % and 70 % yield of 5, respectively. The synthesis of 5 from 2 [58] using BuSnCl 3 as the catalyst (230°C, 3 h) has also been explored and 5 was obtained in 60 % yield.…”
Section: Two-step Synthetic Approach Viamentioning
confidence: 99%
“…Synthetic methodology for the synthesis of 5 has been reported; examples are the oxidative cyclization reaction of 5-hexen-1-ol [55][56][57] using TS-1 (60°C, 6 h) [55,56] or a PNIPAAm-PW 12 O 40 3-complex (60°C, 6 h) [57] to give 90 % and 70 % yield of 5, respectively. The synthesis of 5 from 2 [58] using BuSnCl 3 as the catalyst (230°C, 3 h) has also been explored and 5 was obtained in 60 % yield.…”
Section: Two-step Synthetic Approach Viamentioning
confidence: 99%
“…126 In the 2-catalyzed oxidative cyclization with hydrogen peroxide in water, the absorption of organic materials in the catalyst phase was similarly detected at 60°C, and higher reactivity owing to the hydrophobic effect was observed. The organic materials retained in gel were released by cooling the reaction mixture, and the organic/aqueous/solid phases were cleanly separated after the addition of diethyl ether.…”
Section: Thermoregulated Gel-phase Systemmentioning
confidence: 70%
“…6). 220) In 11a-catalyzed oxidative cyclization with hydrogen peroxide in water, absorption of organic materials in the catalyst phase was similarly detected at 60°C, and higher reactivity owing to hydrophobic effect was observed. The organic materials retained in gel were released by cooling the reaction mixture and the organic/aqueous/ solid phases were cleanly separated after addition of diethyl ether.…”
Section: Thermoregulated Gel-phase Systemmentioning
confidence: 89%
“…This work focuses much attention on the use of thermoregulated hydrophobic species formed by PNIPAAm as novel organic reaction medium in water. [214][215][216][217][218][219][220] Previously, our group found that an assembled complex of non-cross-linked PNIPAAm copolymer ligands and inorganic salts affords insoluble solids in water and possesses functions as a triphase catalyst. [221][222][223][224] To design a new oxometalate catalyzed oxidation system based on thermomorphic property of PNIPAAm, a dye-labeled catalyst 11b comprising a phosphotungstate anion, a PNIPAAm polymer chain, and a Disperse Red moiety was synthesized (Chart 7).…”
Section: Thermomorphic Property Of Polyoxometalatementioning
confidence: 99%